2015
DOI: 10.1134/s1070363215080319
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new N-phosphorylated vinylhydropyridines

Abstract: It is known that secondary phosphine halides react with electron-deficient acetylenes in the presence of bases [1][2][3][4], radical initiators [1,5, 6], metal complex catalysts [7,8], under microwave irradiation [9], and (rarely) in bulk without any catalyst [10] to form tertiary alkenylphosphine halides and the products of bis-addition.In this work, we performed a three-component reaction of diphenylphosphine sulfide Ia and bis(2-phenylethyl)phosphine selenide Ib with acetylenecarboxylates IIa, IIb and pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…On the example of diethyl acetylenedicarboxylate 21a, pyridine 1a and bis(2-phenylethyl) phosphine selenide 2i, it was shown that internal acetylenes of such a type were less effective in the three-component reaction with pyridines and secondary phosphine chalcogenides [49]. Therefore, at an equimolar ratio of these reagents (room temperature, 1 h) E-isomer of N-ethenyl-1,4-dihydropyridine 22 was formed in a 17% yield (Scheme 16).…”
Section: N-vinylated/c-phosphorylated Pyridines: Delayed S N H Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the example of diethyl acetylenedicarboxylate 21a, pyridine 1a and bis(2-phenylethyl) phosphine selenide 2i, it was shown that internal acetylenes of such a type were less effective in the three-component reaction with pyridines and secondary phosphine chalcogenides [49]. Therefore, at an equimolar ratio of these reagents (room temperature, 1 h) E-isomer of N-ethenyl-1,4-dihydropyridine 22 was formed in a 17% yield (Scheme 16).…”
Section: N-vinylated/c-phosphorylated Pyridines: Delayed S N H Phosphorylationmentioning
confidence: 99%
“…A short time ago [37][38][39][40], the nucleophilic substitution of hydrogen (S N H reaction) in non-activated pyridines and their fused derivatives by secondary phosphine chalcogenides (synthesized from red phosphorus [41][42][43][44]) in the presence of electron-deficient terminal and internal acetylenes was disclosed. These reactions involve the step of N-vinylation/ C-phosphorylation of pyridinoids, and are often retained at this step [45][46][47][48][49]. Afterwards, a series of this finding's follow-up works appeared.…”
Section: Introductionmentioning
confidence: 99%